Short-term effect of anti-VEGF for chronic central serous chorioretinopathy according to the presence of choroidal neovascularization using optical coherence tomography angiography. - Yong-Yeon Song; Hwa-Young Yu; Seung-Kook Baek; Young-Hoon Lee; Min-Woo Lee (PLoS ONE)
Purpose To analyze the short-term therapeutic efficacy of intravitreal injection of bevacizumab (IVB) for chronic central serous chorioretinopathy (CSC) according to the presence of choroidal neovascularization (CNV) using optical coherence tomography angiography (OCTA). Methods A retrospective chart review was perfomed on cases of CSC with CNV (Group 1: n = 31) and an age-matched cases of CSC without CNV (Group 2: n = 30). The response to IVB was evaluated by changes in best-corrected visual acuity (BCVA), central macular thickness (CMT), choroidal thickness (CT), and pachyvessel diameter. Univariate and multivariate linear regression analyses were performed to identify factors associated with the visual outcome of chronic CSC with CNV after IVB. Results At baseline, the CT values differed significantly between Groups 1 and 2 (371.55 ± 67.09 vs. 417.33 ± 71.32 μm, p = 0.01). In Group 1, BCVA improved significantly (p < 0.001), and CMT (p < 0.001), CT (p = 0.001) and pachyvessel diameter (p = 0.045) decreased significantly, after IVB. In Group 2, only pachyvessel diameter (p = 0.001) was significantly smaller after IVB. Univariate analysis showed that the initial CT (B = 0.002, p = 0.026) and pachyvessel diameter (B = 0.002, p = 0.001) significantly affected visual outcome. In multivariate analysis, the initial pachyvessel diameter exhibited significant results (B = 0.002, p = 0.001). Conclusions IVB showed less effective short-term outcomes in chronic CSC patients without CNV than in patients with CNV. In chronic CSC with CNV, the short-term visual outcome after IVB was better in patients with a thinner choroid and smaller pachyvessels.